Legitimizing Empire : Filipino American and U.S. Puerto Rican Cultural Critique - Caronan, Faye, 1979- (Book collections on Project MUSE., 2015)
"After the Spanish-American War, the United States acquired overseas colonies and became an empire. Since the advent of U.S. colonialism in the Philippines and Puerto Rico, to reconcile its new status as an overseas empire with its anticolonial roots, the United States distinguished itself from European empires by claiming that it would altruistically establish democratic institutions in its colonies. In response, Filipino and Puerto Rican artists have challenged the promises of benevolent assimilation to demonstrate how U.S. imperialism is inherently self-interested, not exceptional among empires. Faye Caronan examines Puerto Rican and Filipino/American cultural productions as pivotal engagements with U.S. imperial exploits in these two terrains. Caronan skillfully interprets novels, films, performance poetry, and other cultural productions as both symptoms of and resistance against American military, social, economic and political incursions into these territories. Today the Philippines is an independent nation whereas Puerto Rico is a U.S. commonwealth, but somehow both remain subordinate to America. The different colonial relations mean that the Philippines and Puerto Rico cannot serve the same function in justifying U.S. imperialism. Caronan's juxtaposition reveals two different yet simultaneous models of U.S. neocolonial power and contradicts American exceptionalism as a reluctant empire that only accepts colonies for the benefit of the colonized and global welfare"--